Feasibility Analysis of Teaching Materials with Pirolysis Tool in SMA Lubuklinggau City - Endang Lovisia; Wahyu Arini (Jurnal Pembelajaran Fisika, 2020)
This research purpose to develop physics modules based on the subject of temperature and heat in class X students of Lubuklinggau State High School, and produce valid physics modules. The development of this research uses the ADDIE model with five stages namely analysis, design, development, implementation, and evaluation. Module validity was obtained from the results of expert validators namely material experts with a percentage of 82.23%, media experts with a percentage of 81.94%, and linguists with a percentage of 77.31% with a very good category. The conclusion obtained is the physics module of temperature and color. In terms of the experts, the material is valid with very good criteria, the linguist is categorized as valid with very good criteria and the media experts are valid with very good criteria.Keywords: Feasibility, teaching materials, physics moduleDOI: http://dx.doi.org/10.23960/jpf.v8.n1.202011